Sexual Assault, Pregnancy and HIV Infection among Young Girls in the Transkei Region of South Africa. Case Reports - B Meel (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Rape continues to be one of the biggest challenges facing South Africa, alongside poverty & joblessness that the government is trying hard to eradicate. Transkei region of the Eastern Cape can best be described as deeply rural with bad roads, unclean water supply, limited electricity, few telephone connections, very limited access to transport and health services. Violence including sexual assaults is a common problem in this region. Objective: To highlight the problem of sexual assault, pregnancy, and HIV infection among young girls in Transkei region of South Africa. Case History: This is a retrospective case report from the register of sexual assault at Sinawe Center of Mthatha General Hospital, Mthatha, South Africa.These are reports of two young girls who were repeatedly raped. Histories and findings of the physical examinations are described. Consequences of teenage pregnancies and HIV transmission are discussed. The issue of consent and teenagers’ partners’ responsibility is highlighted. Solutions to reduce re-victimisation are suggested. Conclusion: There is problem of sexual assaults, pregnancy, and HIV infection among young girls in the Transkei region of South Africa. There is a need to control this epidemic of sexual assaults to prevent HIV spread, and to prevent unwanted pregnancies